Effects of electric field on microstructure evolution and defect formation in flash-sintered TiO2. Issue 13 (October 2022) - Yang, Bo; Shang, Zhongxia; Li, Jin; Phuah, Xin Li; Cho, Jaehun; Wang, Haiyan; Zhang, Xinghang
Abstract: Various ceramic materials have been successfully flash sintered via mostly direct current (DC) and some by alternative current (AC). However, a direct comparison on the effects of different field types on the overall microstructure and atomistic defect distribution in flash-sintered ceramics is still very limited. In this work, rutile TiO2 was chosen as a model system to directly compare the effects of DC and AC fields on microstructure and defect distribution. DC flash-sintered TiO2 presents asymmetrical distributions of grain sizes and defects, while AC sintered TiO2 have more homogeneous microstructures. More interestingly, we demonstrated a reverse-polarity flash sintering technique can achieve dense TiO2 bulk samples with homogeneous microstructure and tunable defect gradient, which are previously not attainable from either DC or AC sintering alone. This study shows the importance of field on the microstructures of flash-sintered ceramics and the great potential in achieving dense and uniform microstructures via effective field control process.